The pursuit of power and security: the influence of natural resources and geography on Athenian foreign policy - Sergidis, Kristis (2012)
The aim of this thesis is to define and explore the role of natural resources and the strategic value of geography for Athenian foreign policy, focussing particularly on the fifth and fourth centuries. In spite of the established position of natural resources in studies of Greek economic and political history, there remains no comprehensive treatment of the interrelationship between natural resources and the formulation of Athenian foreign policy. The thesis exploits the approaches established by previous scholarship, advances in epigraphy, modern studies of geography and classical philology to examine these two aspects, focussing primarily on the role of timber, grain, precious metals, red ochre, sea-routes and islands within Athenian foreign policy.